Novel Nonlinear Pendula Devices for Wave Energy Extraction - Terrero Gonzalez, Alicia (Curtin University, 2023)
The vast wave energy potential has positioned Wave Energy Converters (WEC) as emerging technologies. This study presents a novel coupled two-pendula device that will be able to harvest energy from pendula rotatory motions when harmonically excited from the base by sea waves. The novel concept is designed, and the system dynamics is investigated numerically and experimentally to obtain optimum system parameters leading to pendula synchronized antiphase rotations, which leads to higher energy outputs.